Kvalificeret selvbestemmelse i klinisk psykologisk arbejde - O’Toole, Mia Skytte; Tønnesvang, Jan (Psyke & Logos, 2015)
A large number of named psychotherapies provides clinicians with a broad catalogue from which to pick and choose intervention techniques. Today, many psychotherapists claim to work eclectically, referring to the use of varying intervention techniques both within and between the different psychotherapeutic traditions. The availability of many psychotherapeutic techniques can indeed be beneficial, but the question remains as to how the psychotherapist chooses one technique over another depending on the circumstances. In this paper, we will present an analytic framework aimed at providing psychotherapists with a navigation tool with which to qualify the choice and coordination of psychotherapeutic techniques. The foundation for this tool is the concept of qualified self-determination, which points to some of the basic competencies necessary for humans to navigate within the technical, social, and personal domains of life. On this basis, we outline how different psychotherapies are differentially aimed at developing these competencies. Finally, we present specific examples on where and how this framework can be used, including how it can guide the client case formulation, and how it can facilitate productive collaboration at network meetings.